Pengaruh Inventory Intensity, Capital Intensity, Sales Growth Dan Beban Iklan Terhadap Agresivitas Pajak - Farina Jessen Yap (CV. Ulil Albab Corp, 2024)
Tax aggressiveness, namely the company's desire to reduce the amount of tax burden that must be paid either legally (Tax Avoidance) or illegally (Tax Evasion) by exploiting the gaps in tax regulations. The more likely the company is to reduce the amount of tax burden, the more aggressive the company will be towards taxes. The research objective was to determine and analyze the effect of Inventory Intensity, Capital Intensity, Sales Growth and Advertising Expenses on Tax Aggressiveness at PT. Sumber Buana Perkasa Medan for the period 2020-2023. This type of research is a quantitative study using observation data collection techniques, interviews and documentation. The data analysis technique used is multiple linear regression analysis, classical assumption test and hypothesis testing. The results of this study indicate that simultaneously inventory intensity, capital intensity, sales growth and advertising expenses have a significant effect on tax aggressiveness at PT. Sumber Buana Perkasa period 2020-2023. Partially capital intensity, sales growth and advertising expenses have a significant positive effect on tax aggressiveness while inventory intensity has a significant negative effect on tax aggressiveness. The conclusion of this study is inventory intensity, capital intensity, sales growth and advertising expenses have an effect on tax aggressiveness at PT. Sumber Buana Perkasa for the period 2020-2023, the remaining 29.9% was influenced by other variables of 70.1% such as leverage, profitability and others